Effects of Combining Occupationally Relevant Physical and Cognitive Tasks. A Systematic Review. - Mixter, Susanna; Mathiassen, Svend Erik; Jahncke, Helena; Lyskov, Eugene; Hallman, David M; Lewis, Charlotte (Annals of Work Exposures & Health, 2023)
Objectives Physical and cognitive tasks occur together in many occupations. Previous reviews of combined tasks have mainly focused on their effects in a sports context. This review investigated to which extent combinations (concurrent or alternating) of occupationally relevant physical and cognitive tasks influence responses reflecting biomechanical exposure, stress, fatigue, performance, and well-being. Methods We searched Scopus, Pubmed, Cinahl, and Psychinfo for controlled experiments investigating the effects of combinations of occupationally relevant physical and cognitive tasks in participants aged 18 to 70. In total, we identified 12 447 records. We added recent papers that had cited these studies (n = 573) to arrive at a total of 13 020 publications. After screening for relevance, 61 studies remained, of which 57 were classified to be of medium or high quality. Of the 57 studies, 51 addressed concurrent tasks, 5 alternating tasks, and 1 both concurrent and alternating tasks. Results Most studies of concurrent physical and cognitive tasks reported negative effects, if numerically small, on indicators of biomechanical exposure, fatigue, and performance, compared to a physical task alone. Results were mixed for stress indicators, and well-being was too little studied to justify any conclusions. Effects depended on the tasks, including their intensity and complexity. Alternating physical and cognitive tasks did not appear to influence outcomes much, compared to having passive breaks in-between physical tasks. Conclusions The reviewed evidence indicated that concurrent physical and cognitive work tasks have negative, yet small effects on biomechanical indicators, fatigue and performance, compared to performing the physical task alone, but only if the physical task is intense, and the cognitive task is complex. Alternating between physical and cognitive tasks may have similar effects as breaking up physical tasks by passive breaks, but studies were few. Future studies should address ecologically valid combinations of physical and cognitive tasks, in particular in controlled field studies devoted to the long-term effects of combined work.